2013
DOI: 10.1111/jmp.12055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gluten on clinical and immunological status of common marmosets (Callithrix jacchus)

Abstract: Gluten ingestion caused gastrointestinal symptoms in common marmosets, which disappeared on gluten withdrawal. Considering the immunological response to both diets, gluten sensitivity seems to be most likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Clinical and pathological findings for marmosets with duodenal dilation (Case Nos [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. and control animals.…”
mentioning
confidence: 99%
“…Clinical and pathological findings for marmosets with duodenal dilation (Case Nos [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. and control animals.…”
mentioning
confidence: 99%
“…While theoretically plausible, more than 80% of diets in this survey contained wheat gluten, which was disproportionate to the number of animals with MWS. A laboratory based study on tamarins and gluten noted that tamarins did not display a high immune reaction to the gliadin protein found in gluten (Kuehnel et al, ). Only 12 out of the 40 tamarin specimens used in that study showed acute immune reaction to the presence of wheat gluten in their diet, but not all of these individuals had MWS related signs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fiber in the diet also modulates the insulin resisting effect of soluble carbohydrates (Roberfroid, 1993). In previous studies where gluten free diets were shown to be beneficial for MWS, the fiber content was also increased and this may have contributed to their positive results (Kuehnel et al, 2013). Removing or reducing fruit from diets and replacing them with vegetables will also reduce soluble carbohydrates and increase fiber fractions, perhaps giving the same positive results (Britt et al, 2015;Cabana & Nekaris, 2015).…”
Section: The Fiber Hypothesismentioning
confidence: 98%
“…Weight loss and wasting are nonspecific signs in marmosets and may be associated with a number of clinical entities. These findings have been associated with parasitic infection [36,88e90], gluten sensitivity [91], dietary protein deficiency [92,93], vitamin E deficiency [23], stress, and gliadin hypersensitivity [94,95]. In one survey of zoos, no fewer than 10 causes were proposed by survey respondents [96].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Additional investigations into dietary factors would be worthwhile. Recent reports of gluten sensitivity including elevations in anti-Gliadin antibodies and positive response to food trials eliminating gluten indicate that dietary factors, specifically incorporation of cereals into the diet, may play a role in the development of IBD [91,94,95]. Furthermore, in one…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%